2003
DOI: 10.1093/nar/gkg236
|View full text |Cite
|
Sign up to set email alerts
|

The highly related DEAD box RNA helicases p68 and p72 exist as heterodimers in cells

Abstract: The RNA helicases p68 and p72 are highly related members of the DEAD box family of proteins, sharing 90% identity across the conserved core, and have been shown to be involved in both transcription and mRNA processing. We previously showed that these proteins co-localise in the nucleus of interphase cells. In this study we show that p68 and p72 can interact with each other and self-associate in the yeast two-hybrid system. Co-immunoprecipitation experiments confirmed that p68 and p72 can interact in the cell a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(85 citation statements)
references
References 38 publications
(62 reference statements)
3
81
1
Order By: Relevance
“…p72 could be a candidate for this redundant function. It was recently demonstrated that p68 and p72 exist as a heterodimer in cells (34). Furthermore, p72 was shown to associate with the U1 snRNP (24), and the protein plays a role in regulating the splicing of alternative exons containing AC-rich exon enhancer elements (15).…”
Section: Discussionmentioning
confidence: 99%
“…p72 could be a candidate for this redundant function. It was recently demonstrated that p68 and p72 exist as a heterodimer in cells (34). Furthermore, p72 was shown to associate with the U1 snRNP (24), and the protein plays a role in regulating the splicing of alternative exons containing AC-rich exon enhancer elements (15).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids expressing WT and K53R/E55A mutant p68 included untagged versions in pcDNA3 (Invitrogen), as well as myc epitope-tagged versions in pSG5 (Stratagene, La Jolla, CA, USA), GAL4-tagged versions (in a pcDNA3 derivative expressing amino acids 1-147 of GAL4 (Wilson et al, 2004)) and GST-tagged versions in pEBG2T (Ogilvie et al, 2003). Plasmids expressing His-tagged SUMO-1, SUMO-2 and SUMO-3 were generated in pcDNA3; the plasmid expressing myc-tagged PIAS1 was in pSG5; plasmids expressing HAtagged PIAS1 and PIASy were in pKW2T (a gift from Mienrad Busslinger, Vienna Biocentre, Austria); Luciferase reporter plasmids included the p53-responsive PG13-Luc (el-Deiry et al, 1993) and pTK-Luc bearing two copies of the GAL4-binding site (a gift from Brian Wilson, McGill University, Montreal, Canada).…”
Section: Plasmidsmentioning
confidence: 99%
“…GST pulldowns GST-tagged p68 and vector control were expressed in 293 cells as described previously (Ogilvie et al, 2003) and purified on glutathione beads using standard conditions. PIAS1 and PIASy were translated in vitro using the TNT kit from Promega and GST pulldowns were performed as described previously (Hsieh et al, 1999).…”
Section: Antibodiesmentioning
confidence: 99%
“…P72, a human nuclear DEAD box protein and a very close homologue of P68, has recently been shown to form heterodimers with P68 in vivo (Ogilvie et al, 2003). P72 has a predominantly granular nucleoplasmic staining pattern, excluding nucleoli, like P68 (Lamm et al, 1996).…”
Section: Intranuclear Localisation Of P68mentioning
confidence: 99%